Penerapan Green Accounting Terhadap Pengelolaan Limbah pada Rumah Sakit Swasta Bandar Lampung - Tambunan, Petrus Hamonangan; Aminah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
In recent decades, the issue of environmental damage has become a global concern, and hospitals as health care institutions play an important role in medical waste management. This study uses a quantitative approach with regression analysis to test the influence of environmental accounting cost components, namely prevention costs, detection costs, internal failure costs, and external failure costs, on waste management. The results of the analysis show that all variables have a positive and significant effect on waste management. The implementation of good environmental accounting can increase the effectiveness of waste management, support environmental sustainability, and make a positive contribution to public health.